Green Innovation and Competitive Advantage: The Mediating Impact of Corporate Image - Afif, Naufal Ijlal; Susilowati, Christin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the effect of green innovation on competitive advantage with corporate image as a mediating variable among consumers of Retrorika Coffee Batu. Design/Methodology/Approach – This study employs a quantitative research approach. Data were collected from 250 consumers of Retrorika Coffee Batu as respondents. The research instruments were tested using validity and reliability tests, while the data were analyzed using Partial Least Squares (PLS) to examine the direct and indirect relationships among green innovation, corporate image, and competitive advantage. Findings – The results indicate that green innovation has a significant effect on competitive advantage. Corporate image also has a significant effect on competitive advantage. Furthermore, corporate image significantly mediates the relationship between green innovation and competitive advantage. These findings suggest that implementing environmentally friendly innovations while strengthening a positive corporate image can enhance a company’s competitive position in a market increasingly concerned with sustainability. Originality/Value This research is original in testing corporate image as a mediating variable between green innovation and competitive advantage in a local coffee shop context. The findings provide practical value by guiding businesses to leverage sustainability initiatives to strengthen brand image and market positioning.